(3JaSjQ ShQI GdfHCs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3Ye GUdg YfeG Ydi Efg MQa LQ heG GdGSJagGejI hobQjA Ydi GdCUd de MPaJ GdGda s
(3BNQgG (B:s
(3cfJ JQGHkG Ci Mjf eJ eG cGf SGFQ GdMjhGfGJ aEf GdGfSGf eNUhU ef HjfgG HGdQhM GdHGbi Je Jfejb GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
Keywords: (3GdJaSjQ hYdhe GdbQBfs